(untitled) (Journal of history, 2026)
This article examines the historical relationship between libraries and scholarly communication, tracing the evolution of the role of libraries from knowledge repositories to active participants in the creation, dissemination and preservation of scientific research. It analyzes the institutional transformation of libraries in the context of the development of digital technologies, open access and the changing needs of the scientific community. The research methodology is based on a comprehensive approach. This approach includes content analysis of strategic documents of international organizations (UNESCO, IFLA, OECD), interpretive analysis of scientific communication models (Garvey, Kramer, OSF), as well as thematic analysis of modern scientific libraries. The scientific novelty of the article lies in systematization and deepening of understanding of the historical trajectory of library development in the context of scholarly communication, as well as in proposing a new typology of institutional transformations of libraries caused by technological, social and economic changes. Based on the analysis of national and international practices, the transition of libraries from a linear storage model to network and procedural support of scientific activity is substantiated. Particular attention is paid to new functions of libraries, such as support for scientific publications, research data management and development of digital literacy using the example of university libraries (MIT, KazNU, Nazarbayev University). The main trends in the transformation of libraries are identified, including the transition to digital resources, the development of information services, the formation of new models of interaction with the scientific community and active participation in open science processes. A conclusion is made about the need to institutionalize libraries as active actors in open science policy and STI strategies. The results of the study allow us to better understand the current position of libraries in the scientific communication system and predict their further development in the context of a constantly changing information landscape.